Pattern and Prevalence of Maxillary Canine, A CBCT Based Study - Maham Khalid, Mehmil Aslam, Muhammad Salman Aminwala, Waheed Gul Shaikh, Marium Azfar, Nosheen Khawar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Maxillary canines are considered as the keystone of mouth. It plays main role in supporting the upper lip and biting and tearing of food. Canines are also called as cuspids, the upper one is second most common teeth. The purpose of this research was to find the pattern and prevalence of the maxillary canine. Study design: It is a retrospective study conducted for the duration of six months from April 2022 to September 2022 at the dental department of Karachi Medical and Dental College, Karachi. Material and Methods: The study was conducted on 200 subjects visited the dental sciences department of the hospital. The patients who willingly participated in the study was included. The CBCT data was collected and sorted for the further use. Results: Out of the 200 subjects, the 96 (48%) males and 104 were females. The left buccal quadrant of impaction was observed in the 21 males and 15 females. The 5 male and 10 female subjects have the both buccal impaction position. The 8 male and 10 female have the both platal position of impaction. The prevalence of subtype l was 55% in the female and 44% in the males. The subtype II was observed in the 44% females and 55% males. There was no case of type IV subtype. The type VII prevalence was also higher in female 66% as compared to males 33%. Conclusion: The maxillary canine impaction is higher in the female as compared to the males. The impaction prevalence is most commonly observed on the left side as compared to the right side. It was also observed that the buccal and palatal impaction are predominant than other impactions. Keywords: cuspids, maxillary canine, palatal impaction.